2018
DOI: 10.1647/2017-281
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of a Single Dose of Oral and Intramuscular Meloxicam in African Penguins (Spheniscus demersus)

Abstract: Meloxicam is a nonsteroidal anti-inflammatory drug (NSAID) that has been used orally and intramuscularly in numerous avian species, but not studied to date, in African penguins ( Spheniscus demersus). The study describes the pharmacokinetic parameters of meloxicam after oral and intramuscular administration to African penguins. Several pilot studies were conducted initially where meloxicam (1, 0.5, and 0.25 mg/kg) was given intramuscularly to 4 birds, and orally (1 mg/kg) to 2 birds. Based on pilot study resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…The elimination half-lives of 3.24 h for 1 mg/kg meloxicam and 5.68 h for 2 mg/kg in zebra finches are short relative to those after a single intramuscular dose in Hispaniolan Amazon parrots (15.1 h, 1 mg/kg IM), 10 African grey parrots (35.3 h, 1 mg/kg IM), 12 and African penguins (31.87 h, 0.5 mg/kg IM). 14 Conversely, t 1/2 values in finches were longer than those determined for a single intramuscular dose of meloxicam in American flamingos (1.83 h, 1 mg/kg IM), 2 vultures (0.42 h, 2 mg/kg IM), 15 and lesser flamingos (1.93 h, 0.5 mg/kg IM). 18 Unique properties of protein binding and biotransformation likely influence interspecies differences in meloxicam t 1/2 .…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…The elimination half-lives of 3.24 h for 1 mg/kg meloxicam and 5.68 h for 2 mg/kg in zebra finches are short relative to those after a single intramuscular dose in Hispaniolan Amazon parrots (15.1 h, 1 mg/kg IM), 10 African grey parrots (35.3 h, 1 mg/kg IM), 12 and African penguins (31.87 h, 0.5 mg/kg IM). 14 Conversely, t 1/2 values in finches were longer than those determined for a single intramuscular dose of meloxicam in American flamingos (1.83 h, 1 mg/kg IM), 2 vultures (0.42 h, 2 mg/kg IM), 15 and lesser flamingos (1.93 h, 0.5 mg/kg IM). 18 Unique properties of protein binding and biotransformation likely influence interspecies differences in meloxicam t 1/2 .…”
Section: Discussionmentioning
confidence: 79%
“…Figure 1 depicts the mean plasma concentration of meloxicam at 1 and 2 mg/kg plotted against the 5 time points; the dashed horizontal line shows the plasma concentration (3500 ng/mL) considered to provide analgesia in previous reports regarding various bird species. 2,10,12,14 A noncompartmental model was used to estimate the pharmacokinetic parameters presented in Table 1. Neither T max , t 1/2 , nor elimination rate constants differed significantly between the 2 doses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, t 1/2ʎz following the oral administration of MLX, CRP, and TA was similar to that after IM administration. The t 1/2ʎz for oral route of MLX in different species was similar with IM route (Molter et al, 2013; Montesinos et al, 2016; Morrison et al, 2018). However, the obvious differences in t 1/2ʎz of MLX, CRP, and TA have been reported among species.…”
Section: Discussionmentioning
confidence: 72%
“…It was shown that overdose and long-term administration of anti-inflammatory drugs could induce hematological changes and severe renal damage mediated by oxidative apoptotic proliferative mechanisms and also lead to decreased total antioxidant capacity (Orabi et al 2020;Hashem et al 2021). Anti-inflammatory drug meloxicam shows that preferential inhibition of cyclooxygenase-2 (COX-2) has been used as a safe NSAID in numerous avian species in clinical practice (Morrison et al 2018). This drug with proven pharmacokinetic and efficacy is recommended as a feasible and safe option for the treatment of various conditions in different bird species (Guzman et al 2015).…”
Section: Introductionmentioning
confidence: 99%